2014
DOI: 10.1002/dc.23243
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of high‐risk HPVHybrid Capture II (hrHPV HC2) test using SurePathTM specimens in the prediction of cervical high‐grade squamous lesions

Abstract: Our results show that the false-negative rate of hrHPV HC2 testing on SurePath(TM) specimens for the detection of CIN 2 and CIN 3 is low and comparable to that of ThinPrep® specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Slide preparation procedures from these media are different [1], [2]. Cells are normally collected using a Cervex-Brush (Rovers Medical Devices, Oss, Netherlands) but in PreservCyt cells are rinsed into the medium, dispersed by vortexing, and transferred to a microscope slide after vacuum filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Slide preparation procedures from these media are different [1], [2]. Cells are normally collected using a Cervex-Brush (Rovers Medical Devices, Oss, Netherlands) but in PreservCyt cells are rinsed into the medium, dispersed by vortexing, and transferred to a microscope slide after vacuum filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also showed statistically equivalent performance of HC2 in different media. [7][8][9] On the other hand, there were significant medium-specific performance differences for Cervista and unspecified commercial kits, with Cervista significantly underperforming in SurePath and Digene media compared with ThinPrep and unspecified commercial kits underperforming in ThinPrep compared with SurePath. To our knowledge, there are no published studies evaluating the accuracy of off-label use of Cervista in media other than ThinPrep.…”
Section: Discussionmentioning
confidence: 99%
“…The cobas HPV Test is a fully automated real-time PCR DNA assay that qualitatively detects the presence of 14 HR HPV genotypes (HPV 16,18,31,33,35,39,45,51,52,56,58,59, 66, and 68) in cervical specimens. Results are simultaneously reported as positive or negative for the pooled 12 HR HPV types (HPV 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, and 68) from channel 1 and HPV16 and HPV18 genotypes read individually from channels 2 and 3, respectively.…”
Section: The Cobas Hpv Test Performed On the 4800 Systemmentioning
confidence: 99%
“…1 Human papillomavirus (HPV) is now recognized as a single, necessary cause of cancer of the cervix and has been isolated from the tissue of nearly all cervical cancer cases. 2 Thirteen HPV genotypes are classified as carcinogenic or high risk (HR): 16,18,31,33,35,39,45,51,52,56,58,59, and 68. An additional genotype (66) is classified as possibly carcinogenic.…”
mentioning
confidence: 99%